Comparing the Dosimetric Properties of 6 MeV to 9 MeV electron beam of Varian Clinac 2100C/D Linear Accelerator Using OMEGA-BEAMnrc Monte Carlo Code System - Ibrahim Othman; Ibrahim Salim (AlQalam Journal of Medical and Applied Sciences, 2023)
Aims. This work shows the differences of 6MeV and 9MeV electron beam modes of Varian Clinac 2100CD Linear accelerator (Linac) by investigating their dosimetric data. Methods. The treatment planning used here is the Monte Carlo (MC) OMEGA-BEAMnrc code system, widely used to improve different equipment’s used in radiation therapy. In the present work, the above mentioned Linac was simulated using BEAMnrc MC code system to produce 10x10cm phase space file of 6MeV electron beam. The produced spectra of the beam phase-space and that provided by the International Atomic Energy Agency (IAEA) for the electron beam of 10cmx10cm field of view were modeled, simulated and finally analyzed using BEAMdp. The beam properties studied here are, the fluence, energy fluences, mean energy and angular and spectral distribution of beam components, photons, electrons, positrons and total sum (all components). The produced electron beams were transported in water phantom using DOSXYZnrc code and the central-axis absorbed dose, the beam profiles, and the isodose curves were calculated. The central axis depth-dose curves, dose profiles and isodose curves of the electron beams in water phantom were analyzed using DOSXYZnrc, STATDOSE and DOSXYZ_SHOW code. Results. The results of this study for 6 MeV beam were compared with that previously published for 9 MeV beam. This study showed that the depth at maximum dose dmax for 9MeV beam is higher than that for 6MeV while both profiles have the same trend. The OMEGA-BEAMnrc code system can create the phase space data files accurately and are similar to those provided by IAEA data. Conclusion. Omega Beam Code system can simulate the clinical linear accelerator to produce electron beam which can be used to generate accurate MC dose distributions in water phantom or in patients for the sake of equipment improvements in radiation therapy and for radiation dosimetry purposes.